Upper limb international spasticity study: rationale and protocol for a large, international, multicentre prospective cohort study investigating management and goal attainment following treatment with botulinum toxin A in real-life clinical practice. Issue 3 (18th March 2013) - Turner-Stokes, Lynne; Fheodoroff, Klemens; Jacinto, Jorge; Maisonobe, Pascal; Zakine, Benjamin
Abstract : Objectives: This article provides an overview of the Upper Limb International Spasticity (ULIS) programme, which aims to develop a common core dataset for evaluation of real-life practice and outcomes in the treatment of upper-limb spasticity with botulinum toxin A (BoNT-A). Here we present the study protocol for ULIS-II, a large, international cohort study, to describe the rationale and steps to ensure the validity of goal attainment scaling (GAS) as the primary outcome measure. Methods and analysis design: An international, multicentre, observational, prospective, before-and-after study, conducted at 84 centres in 22 countries across three continents. Participants: 468 adults presenting with poststroke upper limb spasticity in whom a decision had already been made to inject BoNT-A (5–12 consecutive participants recruited per centre). Interventions: Physicians were free to choose targeted muscles, BoNT-A preparation, injected doses/technique and timing of follow-up in accordance with their usual practice and the goals for treatment. Primary outcome measure: GAS. Secondary outcomes: Measurements of spasticity, standardised outcome measures and global benefits. Steps to ensure validity included: (1) targeted training of all investigators in the use of GAS; (2) within-study validation of goal statements and (3) establishment of an electronic case report form with an in-built tracking facility for separation of baseline/follow-up data. Analysis: Efficacy population: all participants who had (1) BoNT-A injection and (2) subsequent assessment of GAS. Primary efficacy variable: percentage (95% CI) achievement of the primary goal from GAS following one BoNT-A injection cycle. Ethics and dissemination: This non-interventional study is conducted in compliance with guidelines for good pharmacoepidemiology practices. Appropriate ethical approvals were obtained according to local regulations. ULIS-II will provide important information regarding treatment and outcomes from BoNT-A in real-life upper limb spasticity management. The results will be published separately. Registration: ClinicalTrials.gov identifier: NCT01020500 .